Sinergi Motivasi Kerja, Budaya Organisasi, dan Lingkungan Kerja dalam Meningkatkan Komitmen Organisasional Pegawai - Rendy Noor Mukhlis Saputra; Much. Imron (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine whether work motivation, organizational culture, and work environment can influence the organizational commitment of employees at the village hall office in Mlonggo sub-district. In this study, the population was 96 employees at the village hall office in Mlonggo sub-district. The sampling technique used was saturated sampling, so that a sample was obtained in accordance with the number of the study population. The researcher used quantitative methodology, conducted validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, t-tests, f-tests, and evaluation of the coefficient of determination. The testing instrument used was SPSS software version 22. The findings of this study clarify that individual work motivation does not affect organizational commitment, although organizational culture and work environment positively and significantly affect organizational commitment. Simultaneously, work motivation, organizational culture, and work environment affect the organizational commitment of employees at the village hall office in Mlonggo sub-district. The percentage contribution of the independent variables of work motivation, organizational culture, and work environment to the dependent variable of organizational commitment is 0.560, or 56%.